Vibration Analysis of Chenderoh Dam Physical Model Spillway Structure due to the Effect of Water Spilling: Numerical and Experimental Validation - Arbain A.; Zawawi M.H.; Ganesan R.; Ghazali M.H.M.; Radzi M.R.M.; Hassan N.H.; Mazlan A.Z.A. (Institute of Physics Publishing, 2023)
Dam can be defined as a barrier built across the river to restrain and control the flow of water. However, the safety of the dam structure can be threatened by the uncertainties vibration induced from internal and external sources. Thus, in this paper, the vibration analysis in terms of Experimental Modal Analysis (EMA) and Operational Deflection Shapes (ODS) are carried out to determine the reliability of the dam structure. This study only focused on the spillway structure of the Chenderoh Dam that located in Perak, Malaysia. For the simulation, a 3D physical model with 1:20 scale is developed using SolidWorks software and simulated using ANSYS software. Whilst, for validation of the simulation results, EMA and ODS experiment are performed on the physical model of the Chenderoh Dam. The validation will be in terms of mode shape, ODS, natural and operating frequencies. From the results, the first natural frequency of the spillway occurred at 220.87 Hz with the maximum deflection of 1.6 mm and the ODS deformation happened at operating frequency of 45 Hz with the amplitude value of 0.003 m. The operating frequency value is far from the natural frequency of 220.87 Hz; thus, the transient vibration only induces a minimal effect on the spillway structure and the spillway is considered safe for the operation. Published under licence by IOP Publishing Ltd.